2009
DOI: 10.1158/0008-5472.sabcs-65
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy use before diagnosis and breast cancer survival in the California teachers study.

Abstract: #65 Background: Breast cancer survival appears to be improved by pre-diagnostic use of hormone therapy (HT), but it is unclear from existing studies whether this is attributable to a direct beneficial effect of HT or because HT use encourages the development of certain tumor types with better prognosis. It is therefore important to examine whether the association between HT use and survival still remains after adequate adjustment for tumor characteristics.
 Methods: The California Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The grey vertical lines indicate the 20th, 50th, and 80th percentile of age. Several previous studies have demonstrated an effect of previous HT use on overall or BC-specific survival [24,28,29,33,42,43], although others did not observe this effect [44]. Some studies also studied the effect of HT on prognosis in ovarian cancer patients [5].…”
Section: Age At Diagnosis (Years)mentioning
confidence: 99%
See 1 more Smart Citation
“…The grey vertical lines indicate the 20th, 50th, and 80th percentile of age. Several previous studies have demonstrated an effect of previous HT use on overall or BC-specific survival [24,28,29,33,42,43], although others did not observe this effect [44]. Some studies also studied the effect of HT on prognosis in ovarian cancer patients [5].…”
Section: Age At Diagnosis (Years)mentioning
confidence: 99%
“…One study investigated distant disease-free survival (DMFS) as a measure of the diseaseʼs metastatic activity and reported a favorable effect of previous HT intake on DMFS [32]. It has been hypothesized that this effect on the OS might be related to a selection bias, as HT users may have better general health [33], are better informed about and more aware of health issues, and have a healthier lifestyle and better access to healthcare providers. Better surveillance and earlier detection of tumors at an earlier stage has been suggested as another reason for better OS rates.…”
Section: Introduction !mentioning
confidence: 99%
“…For breast cancer, it has been hypothesized that women who receive HRT generally have a better health status (Marshall et al, 2009). Although the direction of the influence on overall survival and progression-free survival is the same in the study (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…In patients with breast cancer, it is known that the use of estrogen and combined estrogen/progesterone as HRT before the breast cancer is diagnosed reduces the mortality by about 36 and 63%, respectively (Schuetz et al, 2007;Marshall et al, 2009). It was concluded that HRT before diagnosis leads to a more favorable primary tumor, with a lower incidence of recurrence and a better overall survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…Ebenfalls interessant war, dass das Gesamtüberleben von Frauen mit Hormoneinnahme und nachfolgendem Brustkrebs sich nicht von dem der Frauen mit Placebo und nachfolgendem Mammakarzinom unterscheidet. Ein weiterer Vortrag beschäftigte sich mit dem direkten Einfluss von postmenopausaler Hormontherapie auf das spätere Überleben nach Brustkrebs [2]. Als Patientenkollektiv diente eine Kohorte von 2783 Frauen aus dem California-Teacher-Studienkollektiv (insgesamt 133 479 Frauen), bei denen während der Studie ein Mammakarzinom diagnostiziert wurde.…”
unclassified